Delta Shock Index During Emergency Department Stay Is Associated With in Hospital Mortality in Critically Ill Patients - Huang, Yi-Syun; Chiu, I-Min; Tsai, Ming-Ta; Lin, Chun-Fu; Lin, Chien-Fu (Frontiers in Medicine, 2021)
Background The aim of this study was to analyze the association between delta SI during ED management and in-hospital outcomes in patients admitted to the intensive care unit (ICU). Method This was a retrospective study conducted in two tertiary medical centers in Taiwan from January 1, 2016 to December 31, 2017. All adult nontraumatic patients who visited the ED and who were subsequently admitted to the ICU were included. We calculated delta SI by subtracting SI at ICU admission from SI at ED triage, and we analyzed its association with in-hospital outcomes. SI was defined as the ratio of heart rate to systolic blood pressure. The primary outcome was in-hospital mortality, and the secondary outcomes were hospital length of stay (HLOS) and early mortality. Early mortality was defined as mortality within 48 hours of ICU admission. Result During the study period, 11,268 patients met the criteria and were included. Their mean age was 64.5±15.9 years old. Overall, 5,830 (51.6%) patients had positive delta SI. Factors associated with a positive delta SI were multiple comorbidities (51.2% vs. 46.3%, p<0.001) and high Simplified Acute Physiology Score (39 [29-51] vs. 37 [28-47], p<0.001). Patients with positive delta SI were more likely to have tachycardia, hypotension, and higher SI at ICU admission. In regression analysis, high delta SI was associated with in-hospital mortality (aOR [95% CI]: 1.21 [1.03 - 1.42]) and early mortality (aOR [95% CI]: 1.26 [1.07 - 1.48]), but not for HLOS (difference [95% CI]: 0.34 [-0.48 to 1.17]). In the subgroup analysis, high delta SI had higher odds ratios for both mortality and early mortality in elderly (aOR [95% CI]: 1.59 [1.11 - 2.29]) and septic patients (aOR [95% CI]: 1.54 [1.13 - 2.11]). It also showed a higher odds ratio for early mortality in patients with triage systolic blood pressure (SBP) < 100 mmHg (aOR [95% CI]: 2.14 [1.21 - 3.77]) and patients with triage SI ≥ 0.9 (aOR [95% CI]: 1.62 [1.01 - 2.60]). Conclusion High delta SI during ED stay is correlate with in-hospital mortality and early mortality in patients admitted to the ICU via ED.